2016
DOI: 10.1016/j.psychres.2016.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary response abnormalities in depressive disorders

Abstract: Depressive disorders lack objective physiological measurements to characterize the affected population and facilitate study of relevant mechanisms. The melanopsin-mediated light signaling pathway may contribute to seasonal variation and can be measured non-invasively by pupillometry. We prospectively studied changes in melanopsin-mediated pupillary constriction in 19 participants with major depressive disorder (MDD) and 10 control across the summer and winter solstices. The melanopsin-mediated response, as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 37 publications
7
47
2
Order By: Relevance
“…A recent study, however, observed no difference in the PIPR in patients with MDD including SAD compared to healthy individuals (Laurenzo et al, 2016). The discrepancy in the PIPR results among the patients with depression between the two studies may have occurred due to the PIPR measurements in the (Laurenzo et al, 2016) study being conducted during both the winter and summer months when depression and remission occur respectively, possibly altering the melanopsin function with season (Münch, Kourti, Brouzas, & Kawasaki, 2016).…”
Section: Chapter 1: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…A recent study, however, observed no difference in the PIPR in patients with MDD including SAD compared to healthy individuals (Laurenzo et al, 2016). The discrepancy in the PIPR results among the patients with depression between the two studies may have occurred due to the PIPR measurements in the (Laurenzo et al, 2016) study being conducted during both the winter and summer months when depression and remission occur respectively, possibly altering the melanopsin function with season (Münch, Kourti, Brouzas, & Kawasaki, 2016).…”
Section: Chapter 1: Introductionmentioning
confidence: 90%
“…Several studies have linked the role of the recently discovered inner retinal melanopsinexpressing intrinsically photosensitive Retinal Ganglion Cells (ipRGCs) to the regulation of effect of light on mood and cognitive functions in humans (Laurenzo, Kardon, Ledolter, Poolman, Schumacher, Potash, Full, Rice, Ketcham, Starkey, & Fiedorowicz, 2016;Roecklein, Wong, Ernecoff, Miller, Donofry, Kamarck, Wood-Vasey, & Franzen, 2013) and animals (Legates, Altimus, Wang, Lee, Yang, Zhao, Kirkwood, Weber, & Hattar, 2012).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
See 3 more Smart Citations